Assessment of Use of the COBAS AMPLICOR System with BACTEC 12B Cultures for Rapid Detection of Frequently Identified Mycobacteria - Ninet, B. (American Society for Microbiology, 1999)
The use of the COBAS AMPLICOR System (Roche Molecular Diagnostics, Basel, Switzerland), the only automated system for PCR testing, was evaluated for a rapid identification of mycobacteria with positive BACTEC 12B cultures. Two hundred ninety-six specimens with a growth index of ≥30 were analyzed for the presence of Mycobacterium tuberculosis complex, Mycobacterium avium, and Mycobacterium intracellulare. Compared to traditional methods and provided that samples with PCR inhibition are retested at a 1:10 dilution, the sensitivity and specificity of the COBAS AMPLICOR System with BACTEC 12B cultures were 100 and 98%, respectively. The COBAS AMPLICOR method is rapid and reliable for identifying the most common mycobacteria in cultures.